Influence of the painting medium on the alteration process of smalt in oil paintings studied using combined K and Co K-edge XANES - de Mecquenem, Clément; Eveno, Myriam; Zurbach, Damaris; Mösl, Kristina; Cotte, Marine; Reiche, Ina (Applied physics. A, Materials science & processing, 2024)
This study investigates the alteration processes affecting the smalt pigment in historical artworks through a combination of analytical techniques including X-ray Absorption Near Edge Structure (XANES) spectroscopy at the potassium (K) and cobalt (Co) K-edges, coupled with scanning electron microscopy with energy-dispersive X-ray spectroscopy (SEM-EDX) and micro X-ray fluorescence elemental mapping (µ-XRF). Laboratory mock-up samples prepared with different oil binding media were artificially aged, revealing varying rates of smalt degradation. µ-XANES analyses at the K K-edge provided grain-scale insights into smalt alteration, highlighting the influence of binding media composition on degradation kinetics. Crossed clustering data analysis over K µ-XANES acquired on both model samples and historical cross-sections corroborated findings and identified distinct spectral signatures associated with different stages of smalt degradation. Furthermore, identification of potential transformation products such as potassium alum in historical samples emphasized the dynamic nature of pigment alteration processes.